Caring Science Conscious Dying: An Emerging Metaparadigm. (January 2017) - Rosa, William; Estes, Tarron; Watson, Jean
Caring science is an extant theory of human relationship, guiding the profession of nursing with the understanding and application of a moral-ethical praxis that promotes, protects, and provides human dignity throughout the life continuum. Over the past 30 or more years, caring science has transformed nursing by calling for a heightened ethical perspective of human dignity in how nurses practice, educate, research, and evolve the profession. Conscious dying is a framework rooted in a human caring ontology, which strives to deepen the nurse healer's awareness in tending to a patient's dying and death, returning death to its sacred place in the cycle of life. Reflective inventories are self-reflection tools that have been used to encourage nurses' personal growth and development and may be utilized in individual or group settings. The purpose herein is to introduce an emerging metaparadigm that links self to system, interweaving and integrating the teachings of caring science and conscious dying through the use of reflective inventories for both the individual nurse and collective of nursing.